RasGRF2 promotes migration and invasion of colorectal cancer cells by modulating expression of MMP9 through Src/Akt/NF-κB pathway. Issue 4 (3rd April 2019) - Lu, Peifen; Chen, Junjun; Yan, Lihong; Yang, Lijun; Zhang, Litao; Dai, Jie; Hao, Zixuan; Bai, Tao; Xi, Yanfeng; Li, Yahui; Kang, Zhiming; Xv, Jun; et al.
ABSTRACT: Ras-specific guanine nucleotide-releasing factor 2 (RasGRF2) is a member of the guanine nucleotide exchange factors family which is expressed in a variety of tissues and cancer. However, the role of RasGRF2 in cancer is less reported, especially in colorectal cancer(CRC). Hence, the present study aimed to investigated the function of RasGRF2 and ways in which it affects tumor progression in CRC samples and cell lines. We first measured RasGRF2 mRNA level in 26 paired tumor and nontumor colon tissues after colon cancer surgical resection, and determined RasGRF2 protein level in 97 paired paraffin-embedded colon cancer tissues, and found that levels of RasGRF2 mRNA and protein were increased in colorectal tumor tissues, compared with adjacent non-tumor tissues. We then examined the effects of RasGRF2 knockdown on proliferation, migration and invasion were analyzed in CRC cells (SW480, HCT116 and LS174T). HCT116 cells with RasGRF2 knockdown were injected into the tail vein in nude mice to yield metastatic model, and tumor metastasis was measured as well. We found that knockdown of RasGRF2 in CRC cells reduced their migration and invasion in vitro and metastasis in mice. Furthermore, we explored the underlying molecular mechanism for RasGRF2-mediated CRC migration and invasion. The results showed that knockdown of RasGRF2 in CRC cells impairing the expression of MMP9 and inhibiting the activation of Src/Akt and NF-κB signaling. We conclude that RasGRF2 plays a role in controlling migration and invasion of CRC and modulates the expression of MMP9 through Src/PI 3-kinase and the NF-κB pathways.